Aging-associated immune system changes in multiple myeloma: The dark side of the moon. (2021) - Visram, Alissa; Kourelis, Taxiarchis V.
Abstract: Multiple myeloma (MM) is a disease of the elderly. Changes that occur in the immune system with aging, also known as immunosenescence, have been associated with decreased tumor immunosurveillance and are thought to contribute to the development of MM and other cancers in the elderly. Once MM establishes itself in the bone marrow, immunosenescence related changes have been observed in the immune tumor microenvironment (iTME) and are driven by the malignant cells. The efficacy of novel immunotherapies used to treat MM has been blunted by detrimental iTME changes that occur at later disease stages and are, to some extent, driven by prior therapies. In this review, we discuss general changes that occur in the immune system with aging as well as our current knowledge of immunosenescence in MM. We discuss the differences and overlap between T cell senescence and exhaustion as well as potential methods to prevent or reverse immunosenescence. We focus predominantly on T cell immunosenescence which has been better evaluated in this disease and is more pertinent to novel MM immunotherapies. Our lack of understanding of the drivers of immunosenescence at each stage of the disease, from precursor stages to heavily pretreated MM, represents a major barrier to improving the efficacy of novel and existing therapies.